Teacher Misconceptions: A Phenomenon of the Lack of Knowledge in Science Subjects - Dyah Aniza Kismiati; Leonard R. Hutasoit (Jurnal Penelitian Pendidikan IPA, 2024)
Qualified teachers are a cornerstone of successful learning. This study aims to determine the understanding of teachers in elementary schools on the concept of photosynthesis in science subjects in elementary schools. This type of research is survey research. This survey was conducted on 29 elementary school teachers in South Tangerang. Sampling is done randomly (random). The instrument used is a concept statement instrument of 10 statements. The analysis that will be carried out is descriptive by looking at the percentage of misconception scores in each question item. The results showed that there were 3 question items that showed the highest level of misconceptions, with an error range of 86.2% on the presence of chlorophyll, 79.30% on the photosynthesis time item, also 72.4% on results of photosynthesis. The degree of moderate misconception is that 69.00% in statement items related to the role of light in photosynthesis and 62.10% on the photosynthetic product statement item, and. In addition to filling out questionnaires, interviews were also conducted to explore information on why the phenomenon of misconceptions can occur in teachers. The interview results showed that most of the teachers who were sampled for research and teaching science in elementary schools had different educational backgrounds (other than science) as much as 66.00%, 28.00% had science education backgrounds and 7.00% came from other educational backgrounds.